A large size chimeric highly immunogenic peptide presents multistage plasmodium antigens as a vaccine candidate system against malaria (2017)
Rational strategies for obtaining malaria vaccine candidates should include not only a proper selection of target antigens for antibody stimulation, but also a versatile molecular design based on ordering the right pieces from the complex pathogen molecular puzzle towards more active and functional immunogens. Classical Plasmodium falciparum antigens regarded as vaccine candidates have been selected as model targets in this study. Among all possibilities we have chosen epitopes of PfCSP, STARP; MSA1 and Pf155/RESA from pre- A nd erythrocyte stages respectively for designing a large 82-residue chimeric immunogen. A number of options aimed at diminishing steric hindrance for synthetic procedures were assessed based on standard Fmoc chemistry such as building block orthogonal ligation; pseudo-proline and microwave-assisted procedures, therefore the large-chimeric target was produced, characterized and immunologically tested. Antigenicity and functional in vivo efficacy tests of the large-chimera formulations administered alone or as antigen mixtures have proven the stimulation of high antibody titers, showing strong correlation with protection and parasite clearance of vaccinated BALB/c mice after being lethally challenged with both P. berghei-ANKA and P. yoelii 17XL malaria strains. Besides, 3D structure features shown by the large-chimera encouraged as to propose using these rational designed large synthetic molecules as reliable vaccine candidate-presenting systems.